Sc2O3 PVA Film for Switching and Mode-Locking Application in Erbium-Doped Fiber Laser Cavity. Issue 3 (3rd May 2020) - Zulkipli, N. F; Samsamnun, F. S. M.; Rosol, a. H. a; Altuncu, a.; Rusdi, M. F. M.; Mahyuddin, M. B. H.; Khudus, M. I. M. A.; Hanafi, E.; Harun, S. W.
ABSTRACT: We generated Q-switched and mode-locked pulses by making use of the saturable absorption characteristic of scandium oxide (Sc2 O3 ) film, which was obtained by embedding Sc2 O3 nanopowders into polyvinyl alcohol film. The Q-switched laser operated at center wavelength of 1560.5 nm with the maximum pulse energy of 65.6 nJ and 4.4% slope efficiency. With the addition of a 200 m extra single-mode fiber in the ring cavity, a self-starting mode-locked EDFL was implemented. The mode-locked pulses operated at a central wavelength of 1565.4 nm with a repetition rate of 1.0 MHz and a pulse duration of 3.50 ps.